Assistance in the Preparation of SAK EMKM-Based Financial Statements for BUMDes in Supporting Sustainable Governance - Januardi Mesakh; Arthur Simanjuntak; Mitha Christina Ginting; Farida Sagala; Lamria Sagala; Ivo M. Silitonga; Apriani M. Sibarani; Gracesiella Y. Simanjuntak; Duma Rahel Situmorang; Sahala Purba; Arison Nainggolan; Yosephine N. Sembiring (Universitas Methodist Indonesia, 2026)
Village-Owned Enterprises (BUMDes) are one of the key instruments of village economic empowerment that require transparent and accountable financial management. However, most BUMDes managers lack adequate understanding of financial statement preparation based on the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). This community service activity aims to enhance the capacity of BUMDes managers in preparing SAK EMKM-based financial statements to support sustainable financial governance. The methods used were direct mentoring and participatory training involving 25 BUMDes managers in Deli Serdang Regency, North Sumatra. The activities were carried out in three stages: (1) socialization and problem identification, (2) financial statement preparation workshop, and (3) independent mentoring. The results showed a significant increase in participants’ understanding, with the average pre-test score of 42.6 rising to 79.3 in the post-test. A total of 88% of participants successfully prepared simple financial statements in accordance with SAK EMKM standards. This activity contributes to improving the accountability and transparency of BUMDes management as the foundation for sustainable governance.